1995
DOI: 10.1086/647061
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudoepidemic Due to Laboratory Contamination Deciphered by Molecular Analysis

Abstract: The application of molecular typing clearly demonstrated clonality among the isolates and indicated that a common source of contamination, most likely the CMGB tubes, was responsible for these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…We demonstrated that in such cases, RAPD analysis might be a very useful method for determining the clinical relevance of the cultured isolate. For bacterial pathogens, genotyping to determine the clinical relevance of an isolate has been described previously (14).…”
Section: Fig 3 Pcr Typing Of a Fumigatus Isolatesmentioning
confidence: 99%
“…We demonstrated that in such cases, RAPD analysis might be a very useful method for determining the clinical relevance of the cultured isolate. For bacterial pathogens, genotyping to determine the clinical relevance of an isolate has been described previously (14).…”
Section: Fig 3 Pcr Typing Of a Fumigatus Isolatesmentioning
confidence: 99%
“…This situation may result from systemic extrinsic contamination during specimen collection or processing or intrinsic contamination at the time the culture medium 21,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Among the disinfectants commonly used in hospitals, 70 to 90% ethyl alcohol is an excellent intermediate-level germicide but it is not a sporocide. Spore-forming bacteria, such as Bacillus species and Clostridium species, can survive in 70 or 90% ethyl alcohol (2,7,12,15,22). Iodine-containing disinfectant has reliable sporicidal activity (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that 11% of the nosocomial outbreaks were in fact pseudoepidemics (in which an organism is isolated above the normal baseline frequency) (15,17,22). Recognizing and tracking the origin of such pseudoepidemics is difficult and requires the aid of attending physicians, infection control personnel, and clinical microbiologists (12,14).…”
mentioning
confidence: 99%